Role of interactions in a dissipative many-body localized system - Everest, B.; Lesanovsky, Igor; Garrahan, Juan P.; Levi, Emanuele (American Physical Society, 2017)
Recent experimental and theoretical efforts have focused on the effect of dissipation on quantum many-body systems in their many-body localized (MBL) phase. While in the presence of dephasing noise such systems reach a unique ergodic state, their dynamics is characterized by slow relaxation manifested in nonexponential decay of self-correlations. Here we shed light on a currently much debated issue, namely, the role of interactions for this relaxation dynamics. We focus on the experimentally relevant situation of the evolution from an initial charge density wave in the presence of strong dephasing noise. We find a crossover from a regime dominated by disorder to a regime dominated by interactions, with an accompanying change of time correlators from stretched exponential to compressed exponential form. The strongly interacting regime can be explained in terms of nucleation and growth dynamics of relaxing regions—reminiscent of the kinetics of crystallization in soft matter systems—and should be observable experimentally. This interaction-driven crossover suggests that the competition between interactions and noise gives rise to a much richer structure of the MBL phase than anticipated so far.